Pengaruh Penggunaan Minyak Goreng Bekas pada Campuran Asphalt AC-BC - Khaerun Nizam; Anwar Efendy; Aulia Muttaqin; Isfanari Isfanari; Adiman Fariyadin (Universitas Batanghari Jambi, 2026)
This study was conducted to investigate the effect of using waste cooking oil as a partial substitute for asphalt on the Marshall characteristics of Asphalt Concrete – Binder Course (AC-BC) mixtures. The research employed an experimental laboratory method using the Marshall test in accordance with the 2018 General Specifications of Bina Marga. The variations of waste cooking oil used were 1.5%, 2.0%, 2.5%, 3.0%, and 3.5% by weight of asphalt, with an optimum asphalt content of 5.3%. The parameters analyzed included Void in Mix (VIM), Void in Mineral Aggregate (VMA), Voids Filled with Bitumen (VFB), stability, and flow. The results showed that waste cooking oil contents ranging from 1.5% to 3.0% satisfied the requirements of the 2018 Bina Marga Specifications, while the 3.5% variation failed to meet the flow requirement, producing a value of 4.20 mm, which exceeded the specified limit of 2–4 mm. The VIM values ranged from 3.51% to 3.76%, the VMA values ranged from 14.26% to 14.48%, and the VFB values ranged from 74.19% to 75.38%. The highest stability value was obtained at a waste cooking oil content of 1.5%, reaching 1412 kg. Meanwhile, the flow values tended to increase with increasing waste cooking oil content, indicating that the mixture became more flexible due to the reduction in asphalt stiffness. Based on the test results, the most suitable waste cooking oil content was found to be within the range of 1.5%–3.0%, as all Marshall parameters remained within the specified limits. The 3.5% variation is not recommended because its flow value of 4.20 mm exceeded the maximum allowable specification. Furthermore, the utilization of waste cooking oil has the potential to serve as a cost-effective and environmentally friendly alternative material in road pavement construction.